Pemetaan dan Peningkatan Kualitas Layanan Jasa Wisata Pantai Cemara Banyuwangi - Firda Rachma Amalia; Tantri Wijayanti; Ninik Sri Rahayu (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract The research aims to determine the quality of tourism services that most affect the satisfaction of visitors and formulate strategies to improve the quality of Banyuwangi Cemara Beach tourism services. This research uses Servqual method of IPA method (importance Performance Analisys) to know the level of importance and satisfaction of visitors, The research used a sample of 30 respondents who are tourists who have been to Cemara Beach. The result of the research is recommendation of improvement that is 1) The strategy related to entertaiment is as follows: Factors attractions are what can be seen, what can be done what funds can be purchased, the addition of information services, and Realization of the development of facilities on the remaining land accompanied by improvement facilities which has existed ; 2) Strategy related to Managerial that is Optimalization of promotion activity online and non-online, Increase of parking area of vehicle, especially four wheel vehicle, Improve quality of service through training for employees and improve management system of Cemara Beach and Coordinate intensively with stakeholders for improvement and sustainable development. Keyword: quality service, IPA, servqual, Cemara Beach Banyuwangi